#TITLE_ALTERNATIVE# - Rarasati (NIM 19004115), Widita
ABSTRACT: Nowadays, Indonesian Capital market has been growing rapidly. Many theories exist among the academician and investors. Fama and French (1992) made an influence paper according to capital market theory. They disposed many academics thinking on Capital Asset Pricing Model and Efficiency Market hypothesis. Fama and French stated that market risk (beta) did not enough to explain expected return; there are some factors that influence it, such as size and book to market. Therefore, they are proxy for systematic risk which implied that small firm and high book to market should have higher return than big firm and low book to market. This statement and finding also became evidence against efficient market hypothesis. Seasonal effect such as January effect also became evidence against efficiency market hypothesis. Usually, January bring higher return for small and high book to market firm. By using book to market strategy, this paper examines Fama and French theory on capital market. It examines efficiency market hypothesis, Fama and French model, and January effect for Indonesian Capital Market. The result of this paper is not exactly the same as Fama and French. They found that stocks with high book to market have higher return than low book to market. The stocks with high book to market have higher risk compare to stocks with low book to market. In Indonesia, however, the result is contrary to Fama and French theory. Indonesia produces higher return and risk in low book to market portfolio. However, the result shows that Indonesian Capital Market is inefficient because low book to market stocks can outperform market return. This paper also finds that Fama and French multifactor model are applicable for Indonesian Capital Market. It means that one risk factor did not enough to explain average return. This research shows that book to market became one of the factor to explain expected returns. This paper also found that the test for January effect shows a similar pattern with Fama and French, who state that high book to market firm tend to have higher return compare to low book to market in January. Therefore, in Indonesia show the similar tendency for January effect. However, January effect on Indonesia cannot explain multifactor model. The statistics results show while January only is tested, the result is not significant for all variables. Then, when exclude January is tested the result is significant and similar with full sample result. Therefore, it implies that book-to-market strategy is not seasonal phenomenon in Indonesia. In the end of this paper, the results encourage the investor to pick portfolio based on fundamental research and analysis in the expectation that a portfolio of selected stocks can consistently outperform the market. This result suggest that for the period of June 2003 until May 2007, low book to market stocks (growth stock) give higher return compare to high book to market. So, for long term period, it is better for Indonesian investor to hold growth stocks, which have low book to market ratio, and strong in fundamental.